The 'strength of weak ties' among female baboons: fitness-related benefits of social bonds. (April 2017) - McFarland, Richard; Murphy, Derek; Lusseau, David; Henzi, S. Peter; Parker, Jessica L.; Pollet, Thomas V.; Barrett, Louise
Abstract : Studies across a range of species have shown that sociability has positive fitness consequences. Among baboons, both increased infant survival and adult longevity have been associated with the maintenance of strong, equitable and durable social bonds. However, not all baboon populations show these patterns of bonding. South African chacma baboons, Papio ursinus, in the Drakensberg Mountains and De Hoop Nature Reserve show cyclical variation in social relations across time, with strong bonds formed only during certain times of the year. Using long-term data from the De Hoop baboons, we tested whether social relations influence female reproductive success in our study group in a manner similar to other baboon populations. Our results show that the number of strong bonds a female maintained predicted birth rate, and that the number of weak bonds a female possessed predicted infant 12-month survival and infant longevity. Fitness-related benefits of sociability were, however, independent of female dominance rank, and there was no relationship between the number of weak and strong bonds a female maintained. One possible explanation for the influence of weak as well as strong bonds in our study group may be that variation in demographic and ecological conditions across populations may favour the use of different social strategies by females. In our sample, weak bonds as well as strong bonds appear to be instrumental to achieving fitness-related benefits. Highlights: Baboon birth rate is positively predicted by the number of strong bonds shared. 12-month infant survival is positively predicted by the number of weak bonds shared. Infant longevity is positively predicted by the number of weak bonds shared. There is no simple trade-off between the number and quality of social bonds. Social strategies are linked to ecological and demographic variability.